2019
DOI: 10.3390/electronics9010039
|View full text |Cite
|
Sign up to set email alerts
|

Cache Servers Placement Based on Important Switches for SDN-Based ICN

Abstract: In centralized cache management for SDN-based ICN, it is an optimization problem to compute the location of cache servers and takes a longer time. We solve this problem by proposing to use singular-value-decomposition (SVD) and QR-factorization with column pivoting methods of linear algebra as follows. The traffic matrix of the network is lower-rank. Therefore, we compute the most important switches in the network by using SVD and QR-factorization with column pivoting methods. By using real network traces, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…It is better than the original BFR in terms of overhead, latency, and memory. The notion of SDN has been integrated into CCN in some studies [ 30 , 37 ]. To solve the problem of estimating the location of the cache server in the centralized cache management of SDN-based ICN, Badshah et al [ 37 ] used singular value decomposition (SVD) and QR-factorization with column pivoting methods.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It is better than the original BFR in terms of overhead, latency, and memory. The notion of SDN has been integrated into CCN in some studies [ 30 , 37 ]. To solve the problem of estimating the location of the cache server in the centralized cache management of SDN-based ICN, Badshah et al [ 37 ] used singular value decomposition (SVD) and QR-factorization with column pivoting methods.…”
Section: Related Workmentioning
confidence: 99%
“…The notion of SDN has been integrated into CCN in some studies [ 30 , 37 ]. To solve the problem of estimating the location of the cache server in the centralized cache management of SDN-based ICN, Badshah et al [ 37 ] used singular value decomposition (SVD) and QR-factorization with column pivoting methods. The probe -based approach is designed to improve the precision of FIB, especially for the peer-to-peer distributed networks.…”
Section: Related Workmentioning
confidence: 99%
“…In this section, we propose a key link recognition algorithm to recognize the key links in the detection area. Previous work of traffic monitoring provided initial inroads to recognize the key links [10,11]. These work defined the key link as the link delivering the larger traffic flows in the detection area.…”
Section: Key Link Recognitionmentioning
confidence: 99%
“…Previous work of traffic monitoring provided initial inroads to address this challenge [10,11]. Their research results showed that a few key links that deliver larger traffic flows can well represent the traffic load information of all links in the detection area.…”
Section: Introductionmentioning
confidence: 99%
“…Effective caching is another important area that could solve some of the challenges faced by the NDN transport. Significant research is being carried out on the caching issues of ICN [25][26][27][28].…”
Section: The Multisource and Multipath Nature Of Ndn Transportmentioning
confidence: 99%